2018
DOI: 10.1016/j.dcn.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the in vivo adolescent human brain

Abstract: Viscoelastic mechanical properties of the in vivo human brain, measured noninvasively with magnetic resonance elastography (MRE), have recently been shown to be affected by aging and neurological disease, as well as relate to performance on cognitive tasks in adults. The demonstrated sensitivity of brain mechanical properties to neural tissue integrity make them an attractive target for examining the developing brain; however, to date, MRE studies on children are lacking. In this work, we characterized global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 52 publications
8
49
2
Order By: Relevance
“…Indentation experiments, for instance, show that the mouse cerebellum is softer than the mouse cerebrum [108]. This agrees with results on human brain tissue using magnetic resonance elastography [115,123,176]. Finally, it is also important to note that, even within the brain regions we have introduced in Fig.…”
Section: Conclusion Towards Regional Trendssupporting
confidence: 86%
See 1 more Smart Citation
“…Indentation experiments, for instance, show that the mouse cerebellum is softer than the mouse cerebrum [108]. This agrees with results on human brain tissue using magnetic resonance elastography [115,123,176]. Finally, it is also important to note that, even within the brain regions we have introduced in Fig.…”
Section: Conclusion Towards Regional Trendssupporting
confidence: 86%
“…According to magnetic resonance elastography measurements, the adult human brain appears to be three to four times stiffer than the brain of young children [30]. Even adolescent brains still show a softer response than adult brains in certain brain regions including the cerebellum as well as the parietal and temporal lobes [115]. Only one group reported the opposite trend with a decrease in tissue stiffness with age based on indentation and shear experiments on rat brains [62,134].…”
Section: Does Our Brain Stiffen During Development?mentioning
confidence: 99%
“…Previous MRE investigations have found that brain viscoelasticity is affected by neurodegeneration (Murphy et al 2017) and intracranial tumours including cerebral malignancies (Hughes et al 2015;Pepin et al 2015). Adolescent children (McIlvain et al 2018) and older adults (Hiscox et al 2018) also show mechanical property regional variation compared to young adults, suggesting possible developmental trajectories for viscoelastic properties. Emerging evidence suggesting that mechanical signals operate in tandem with biochemical cues to determine tissue characteristics (Chanet and Martin 2014) indicates that brain viscoelasticity may provide novel information related to the underlying integrity of neural tissue microstructure (Sack et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…We adapted the directed differentiation of human oligodendrocytes from hiPSCs that we previously developed (Douvaras et al, 2014;Douvaras and Fossati, 2015) to a well-established system of polyacrylamide (PAAm) hydrogels (Tse and Engler, 2010;Pelham and Wang, 1997;Moshayedi et al, 2010;Jagielska et al, 2012) functionalized to facilitate cell adhesion to their surface ( Figure 1A). The hydrogels mimic a range of stiffness described by Young's elastic modulus E (of magnitude 0.1-70 kPa) that approximates and exceeds the stiffness of the human CNS environment (Murphy et al, 2016;Budday et al, 2017Budday et al, , 2019McIlvain et al, 2018;Urbanski et al, 2019; Figures 1B,C). In other words, these hydrogels span the range of physiological and pathological CNS stiffness.…”
Section: Human Oligodendrocytes Exhibit Mechanosensitive Migration Inmentioning
confidence: 95%